Convex fragmens of strongly minimal Jonsson sets - Yeshkeyev, A.R. (Bulletin of the Karaganda University. Mathematics Series, 2015)
This article introduced and discussed the concepts of minimal Jonsson sets and respectively strongly minimal Jonsson sets. On this basis, we introduce the concept of independence of special subsets of existentially closed submodel of semantic model. The concept of independence leads to the concept of basis and then we have the Jonsson analogue of the theorem on uncountable categoricity.